Does the combined free nitrous acid and electrochemical pretreatment increase methane productivity by provoking sludge solubilization and hydrolysis?. (May 2020) - Niu, Chengxin; Zhang, Zhongyi; Pan, Yang; Tan, Yujie; Lu, Xueqin; Zhen, Guangyin
Graphical abstract: Highlights: Potential of combined FNA and electrolysis for sludge disintegration was assessed. Combined process improved the liberation of particulate to soluble fraction. Methanogenesis was inhibited due to the toxicity of FNA and its derivatives. Increased solubilization of organics does not always improve methane production. Abstract: Free nitrous acid based pretreatments are novel and effective chemical strategies for enhancing waste activated sludge solubilization. In this study, the synergetic effects of the combined free nitrous acid and electrochemical pretreatment on sludge solubilization and subsequent methane productivity were evaluated. The results indicated that pretreatment with 10 V plus 14.17 mg N/L substantially enhanced sludge solubilization, with the highest soluble chemical oxygen demand concentration of 3296.7 mg/L, 25.6-time higher than that without pretreatment (128.9 mg/L). Due to the potential toxicity of NO2 − and NO3 − to microorganisms and its bioprocesses, the methane production of sludge pretreated by free nitrous acid was significantly deteriorated. The maximum methane yield (152.0 ± 9.6 mL/g-VSadded ) was observed at 10 V pretreatment alone, only 1.7% higher than that of the control (149.4 ± 1.6 mL/g-VSadded ). Combined pretreatment indeed enhances the sludge solubilization and hydrolysis, but does not always induce an improved anaerobic digestion efficiency.